2016
DOI: 10.1111/1440-1630.12268
|View full text |Cite
|
Sign up to set email alerts
|

Embracing an occupational perspective: Occupation‐based interventions in hand therapy practice

Abstract: KEY WORDS client-centred practice, information gathering and collaborative goal setting, musculoskeletal/hand therapy, occupational performance, occupational therapy theory and models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 16 publications
4
52
1
1
Order By: Relevance
“…Analysis of the interviews, observations and progress notes indicated that the occupational therapists in this study utilised bottom‐up reasoning processes, assuming that improvements in physical components of the body would result in improved occupational performance and engagement. It has been recognised in the literature that a bottom‐up approach dominates hand therapy research and practice (Fitzpatrick & Presnell, ; Robinson, Brown & O'Brien, ; Winthrop Rose, Kasch, Aaron & Stegink‐Jansen, ). It appeared in this study that the biomedical culture pushed occupational therapists into this way of thinking about body functions and components.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the interviews, observations and progress notes indicated that the occupational therapists in this study utilised bottom‐up reasoning processes, assuming that improvements in physical components of the body would result in improved occupational performance and engagement. It has been recognised in the literature that a bottom‐up approach dominates hand therapy research and practice (Fitzpatrick & Presnell, ; Robinson, Brown & O'Brien, ; Winthrop Rose, Kasch, Aaron & Stegink‐Jansen, ). It appeared in this study that the biomedical culture pushed occupational therapists into this way of thinking about body functions and components.…”
Section: Discussionmentioning
confidence: 99%
“…These informal discussions usually centred on patients’ work and hobbies, which aligns with findings from other studies of hand therapists’ assessment and evaluation practices (Grice, ; Kaskutas & Powell, ; Powell & Von Der Heyde, ). Informal discussion as a way of gathering information may mean patients have difficulty understanding both what information is important to tell the occupational therapist and, the scope of potential areas for intervention (Fitzpatrick & Presnell, ; Robinson et al ., ; Weinstock‐Zlotnick & Bear‐Lehman, ). Occupational issues, including self‐care, may be overlooked during the informal discussion where more obvious leisure or work issues take the forefront, as was for the case for patients following flexor tendon repair in a study by Kaskutas and Powell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparing graduates to practice within a PHC framework thus suggests that hand curricula be positioned within a vision of hand health for all. In addition an occupational perspective would ensure that students consider the total being in his or her lived reality 24 .…”
Section: Introductionmentioning
confidence: 99%